2008
DOI: 10.1038/jp.2008.106
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the current neonatal nurse practitioner workforce

Abstract: Objective: To assess the adequacy and characteristics of the US neonatal nurse practitioner (NNP) workforce.Study Design: Internet-based survey of 271 NNP conference participants. Data were analyzed using SPSS (version 14; Chicago, IL, USA); descriptive statistics, including w 2 -tests of independence, were performed (a ¼ 0.05).Result: Respondents were primarily masters-prepared females, working in level III newborn intensive care units. Unfilled NNP positions were common; time estimated to fill positions aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 19 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Internationally, there was greater evidence of practice scope, activities and patient safety outcomes in this field. However, the evidence comprised largely of descriptive, comparative or before‐and‐after‐studies with minimal evidence of clinical or economic impact (Hall and Wilkinson, 2005, Cusson et al , 2008). For the most part the comparative studies compared junior medical officers with Nurse Practitioner knowledge, skills and interpersonal communication.…”
Section: Neonatal Critical Care Nurse Practitionermentioning
confidence: 99%
“…Internationally, there was greater evidence of practice scope, activities and patient safety outcomes in this field. However, the evidence comprised largely of descriptive, comparative or before‐and‐after‐studies with minimal evidence of clinical or economic impact (Hall and Wilkinson, 2005, Cusson et al , 2008). For the most part the comparative studies compared junior medical officers with Nurse Practitioner knowledge, skills and interpersonal communication.…”
Section: Neonatal Critical Care Nurse Practitionermentioning
confidence: 99%
“…The number of graduates has remained relatively static during the past 4 years (average 260); but, the number of students enrolled has declined in each of the past 4 years from 603 in 2005 to 516 in 2008. 9 One study reported that 63% (123 of 191) of the registered nurses surveyed were not interested in becoming a NNP. The responses indicated 6 categories of reasons, which included the following: (1) obligations to family, (2) too much responsibility in the NNP role, (3) satisfaction in current role, (4) unwilling to work the NNP hours, (5) inadequate pay for NNP role, and (6) cost of education.…”
Section: Nnp Shortagementioning
confidence: 98%
“…In the neonatal intensive care setting, the problem is particularly acute because of the very short supply of ANNPs. The high cost of ANNP education is reducing the number of available NNP programs, and those remaining are not graduating a sufficient number of new ANNPs to keep up with demand 19. Given ANNP shortages, even at the master’s level, the DNP is likely to lead to further ANNP program closures because of faculty shortages 20.…”
Section: Shortage Of Anps and Educatorsmentioning
confidence: 99%